Series Studies in the International Relations The National Security - Massoud, Dr.Abdalla (Dirasat in Economics and Business, 2002)
The national security is an important factor in the international relationsnbjects, though it is the most significat target of the foreign policy for any state. This Concept has been known clearly after the national state- notion, when it became a field of study after ww Il and used conclusively to contain various sides of local and abroud environments particulary when Robert Mecnamra put a new concept that goes beyond the military side to include many questions in the economic development and hence it corrolated with this development. The national Security is that a ction taken liy the stat within its own power to keep its unity and its benefits in the present and in the Future which takes the international changes into consideration.